2013
DOI: 10.1088/0004-637x/765/1/18
|View full text |Cite
|
Sign up to set email alerts
|

RESOLVED DEPLETION ZONES AND SPATIAL DIFFERENTIATION OF N2H+AND N2D+

Abstract: We present a study on the spatial distribution of N 2 D + and N 2 H + in 13 protostellar systems. Eight of thirteen objects observed with the IRAM 30 m telescope show relative offsets between the peak N 2 D + (J = 2 → 1) and N 2 H + (J = 1 → 0) emission. We highlight the case of L1157 using interferometric observations from the Submillimeter Array and Plateau de Bure Interferometer of the N 2 D + (J = 3 → 2) and N 2 H + (J = 1 → 0) transitions, respectively. Depletion of N 2 D + in L1157 is clearly observed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 70 publications
(149 reference statements)
8
65
2
Order By: Relevance
“…The seven VANDAM candidate Class 0 and I disks range in estimated masses of 0.09-0.36 M e . Scaling to our value of k n , Class 0 protostar L1527ʼs disk is 0.013 M e  (Tobin et al 2013) with T d = 30 K. A recent interferometric study of Class I disks in Taurus (Harsono et al 2014) revealed the disks around TMC1A, TMC1, TMR1 and L1536 to have masses of 0.4-3.3 × 10 −2 M e with T d = 30 K and Ossenkopf & Henning (1994) opacities. All mass estimates have uncertainties of a factor of ∼10 due to the unknown gas-to-dust ratio, T d , β, and varying choices of k n .…”
Section: Discussionmentioning
confidence: 51%
“…The seven VANDAM candidate Class 0 and I disks range in estimated masses of 0.09-0.36 M e . Scaling to our value of k n , Class 0 protostar L1527ʼs disk is 0.013 M e  (Tobin et al 2013) with T d = 30 K. A recent interferometric study of Class I disks in Taurus (Harsono et al 2014) revealed the disks around TMC1A, TMC1, TMR1 and L1536 to have masses of 0.4-3.3 × 10 −2 M e with T d = 30 K and Ossenkopf & Henning (1994) opacities. All mass estimates have uncertainties of a factor of ∼10 due to the unknown gas-to-dust ratio, T d , β, and varying choices of k n .…”
Section: Discussionmentioning
confidence: 51%
“…In the chemical models of low mass star formation, a relative enhancement of N 2 H + abundance is expected in the cold prestellar phase, as CO is thought to be depleted in starless cores (e.g. Lee et al 2003;Bergin & Tafalla 2007 central star evolves, the gas gets warm and CO should be evaporated from the dust grains if the dust temperature exceeds about 20 K (Tobin et al 2013). Thus the N 2 H + abundance should decrease as a function of evolutionary stage.…”
Section: Discussionmentioning
confidence: 99%
“…where T 0 = 43 K, derived from a radiative transfer model grid of disks embedded within an envelope that is described in Tobin et al (submitted). The average dust temperature of 43 K is reasonable for a ∼1 L protostar at a radius of ∼50 AU (Whitney et al 2003;Tobin et al 2013). The luminosity is the L bol for each protostellar system measured from the SED (Furlan et al 2016).…”
Section: Dust Continuum Mass and Radius Estimatesmentioning
confidence: 92%